Temperature Control of the 25kW Parabolic Dish-Stirling Engine System - Liaw Geok Pheng; Mohd Ruddin Ab Ghani; Chin Kim Gan; Tole Sutikno (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
This paper is under in-depth investigation due to suspicion of possible plagiarism on a high similarity indexNowadays, even though many researchers continue to investigate and study about Parabolic Dish based on Concentration Solar Power (CSP), the findings are not conclusive and do not provide accurate evidence and proof on the potential of CSP development in Malaysia. The missing link in the Parabolic Dish (PD) Stirling Engine system modelled is the control systems, which vary the amount of working gas in the Stirling engine. The temperature of the heater in PD system which has been modelled is overheated and causes damage to the heater material, low output efficiency, high thermal losses and effect to the lifespan of the PD system. Therefore, the primary aim of this paper was to design a control system to maximize output efficiency during a normal operation by maintaining the heater/absorber temperature at the highest safe operating point and preventing excessive range of threshold to prevent damage to the heater material.